Review Implementation Of Retention Of Medical Record Files Based On The Regulation Of National Standards For Hospital Accreditation (SNARS) Edition 1 MIRM 10 At RSUD Dr RM Djoelham Binjai 2021 - Harefa, Sausan Mawaddah; Mastari , Ekawaty Suryani; Fajar Maulana (SEAN Institute, 2023)
The quality of standardized hospitals in Indonesia can be determined from their alignment with the National Hospital Accreditation Service Standards (SNARS). Medical retention which is also important in hospital services is contained in SNARS First Edition MIRM 10. In MIRM 10 there are three assessments for meeting national hospital accreditation standards regarding retention of medical recovery. The purpose of this study was to determine the implementation of medical record retention at RSUD Dr RM RS Djoelham Binjai based on SNARS 1st Edition MIRM 10. This study used a qualitative descriptive method with a cross sectional design. The research was conducted at Dr.RM Hospital. Djoelham Binjai from June to September 2022. The population in this study were 4 officers and the entire population was sampled. The method used in this research is by interview and observation. Based on the results of the study, it was found that the fulfillment of the 1 MIRM 10 assessment element based on SNARS did not yet have an SOP. Assessment of element 2 has not been fully carried out. The absence of an individual officer for retention duties results in element 3 mismatch. This study concluded that the retention of medical records at RSUD Dr RM Djoelham Binjai had not been fully implemented based on SNARS 1st Edition MIRM 10